2007
DOI: 10.1002/jbm.b.30943
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of hydrophilized porous polymer scaffolds in tissue‐engineered cartilage formation

Abstract: Three dimensional (3D) porous poly(L-lactic acid) (PLLA) scaffolds were fabricated using a modified gas foaming method whose effervescent porogens were a mixture of sodium bicarbonate and citric acid. To improve chondrocyte adhesion, the scaffolds were then hydrophilized through oxygen plasma treatment and in situ graft polymerization of acrylic acid (AA). When the physical properties of AA-grafted scaffolds were examined, the porosity and pore size were 87 approximately 93% and 100 approximately 300 microm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…70 Gas bubbles form by either (1) mixing a foaming or blowing agent, such as sodium bicarbonate, with a pre-polymer where gas is generated upon chemical decomposition 76, 77 or (2) saturating a polymer with subcritical or supercritical gas at high pressure where depressurization results in thermodynamic instability leading to nucleation, growth and coalescence of gas bubbles as illustrated in Figure 3c. 78, 79 Gas foaming does not necessitate the use of organic solvents, but pore formation and porosity depend on rate of nucleation and gas diffusion, which can be difficult to control.…”
Section: Scaffold Fabrication Methodsmentioning
confidence: 99%
“…70 Gas bubbles form by either (1) mixing a foaming or blowing agent, such as sodium bicarbonate, with a pre-polymer where gas is generated upon chemical decomposition 76, 77 or (2) saturating a polymer with subcritical or supercritical gas at high pressure where depressurization results in thermodynamic instability leading to nucleation, growth and coalescence of gas bubbles as illustrated in Figure 3c. 78, 79 Gas foaming does not necessitate the use of organic solvents, but pore formation and porosity depend on rate of nucleation and gas diffusion, which can be difficult to control.…”
Section: Scaffold Fabrication Methodsmentioning
confidence: 99%
“…However, the authors did not examine the effect of these plasma‐polymerized heptylamine coatings on cell adhesion and proliferation. Besides allylamine and heptylamine, also acrylic acid has been plasma‐polymerized on the surface of biodegradable polyesters 154–156. This plasma polymerization method creates hydrophilic surfaces containing a high amount of COOH groups, which can significantly enhance cell attachment and proliferation 154, 155…”
Section: Recent Achievements On Plasma‐based Surface Modification Of mentioning
confidence: 99%
“…Such mechanical property could be related to the water‐uptake ability or swelling ratio of the scaffolds, which is indicative of hydrophilicity . The previous studies have shown that hydrophilic scaffolds supported better cartilage formation through enhanced collagen type II expression and cell redifferentiation in chondrocytes . It is possible that higher hydrophilicity allows for optimal function of the ECM, and thus higher levels of matrix production.…”
Section: Discussionmentioning
confidence: 99%